Relationship Of Family Support With Low-Salt (Sodium) Dietary Adherence In Chronic Renal Failure Patients On Hemodialysis In RSU. Imelda Pekerja Indonesia (IPI) Medan - Silaban, Nataria Yanti; Naibaho, Eka Nugraha V; Siburian, Christine Handayani (Jurnal Kesehatan, Rekam Medis dan Farmasi (JUK-Medifa), 2023)
Hemodialysis is a kidney replacement therapy that is widely used throughout the world and its number is increasing every year (Cleemput &; De-Laet, 2013; Ebrahimi et al., 2016; Yusop et al., 2013). Hemodialysis is performed due to progressive and irreversible kidney damage, so that the kidneys cannot adequately filter toxins and waste products from the blood and (Dorgalaleh et al., 2013). The purpose of the study was to determine the relationship between family support and low-salt (sodium) diet adherence in chronic renal failure patients with hemodialysis in RSU. Imelda Pekerja Indonesia in 2022 This research is a quantitative research using a correlational descriptive design with a cross-sectional observation approach. The results of the study showed a positive and significant relationship between family support and adherence to a low-salt diet (sodium) in patients with Chronic Renal Failure with Hemodilaisa at RSU. Imelda Pekerja Indonesia result p = 0.018. The conclusion of the study was that there was an association of family support with adherence to a low-salt diet (sodium) in CRF patients on hemodialysis at RSU. IPI Medan